Optical properties of ZnMgO films grown by spray pyrolysis and their application to UV photodetection. (7th September 2015) - Lopez-Ponce, M; Hierro, A; Marín-Borrás, V; Tabares, G; Kurtz, A; Albert, S; Agouram, S; Muñoz-Sanjosé, V; Muñoz, E; Ulloa, J M
Abstract: This work presents a comprehensive optical characterization of Zn1− x Mg x O thin films grown by spray pyrolysis (SP). Absorption measurements show the high potential of this technique to tune the bandgap from 3.30 to 4.11 eV by changing the Mg acetate content in the precursor solution, leading to a change of the Mg-content ranging from 0 up to 35%, as measured by transmission electron microscopy-energy dispersive x-ray spectroscopy. The optical emission of the films obtained by cathodoluminescence and photoluminescence spectroscopy shows a blue shift of the peak position from 3.26 to 3.89 eV with increasing Mg incorporation, with a clear excitonic contribution even at high Mg contents. The linewidth broadening of the absorption and emission spectra as well as the magnitude of the observed Stokes shift are found to significantly increase with the Mg content. This is shown to be related to both potential fluctuations induced by pure statistical alloy disorder and the presence of a tail of band states, the latter dominating for medium Mg contents. Finally, metal–semiconductor–metal photodiodes were fabricated showing a high sensitivity and a blue shift in the cut-off energy from 3.32 to 4.02 eV, i.e., down to 308 nm. The photodiodes present large UV/dark contrast ratios (10 2 − 10 7 ), indicating the viability of SP as a growth technique to fabricate low cost (Zn, Mg)O-based UV photodetectors reaching short wavelengths.